Hormetic effect of 17α-ethynylestradiol on activated sludge microbial community response - Budeli, Phumudzo; Ekwanzala, Mutshiene Deogratias; Momba, Maggy Ndombo Benteke (Frontiers in Microbiology, 2022)
Synthetic estrogen analogues are among the most potent estrogenic contaminants in effluents from wastewater treatment plants. Although its effects have been well elucidated in the feminisation of male fish and interference with the endocrine systems in humans, it has not been fully explored in the activated sludge (AS) microbiome, particularly EE2 (17α-ethynylestradiol). Therefore, in this study, the bacterial community shift in a 6-day laboratory-scale reactor in environmental (0, 5, 10 and 100 ng/L) and predictive elevated concentrations (5, 10 and 100 mg/L) of EE2 was investigated using culture-based and metagenomics approaches. Results showed significant changes (t-test, all P < 0.05) between initial and final physicochemical parameters (pH, DO and EC). Although environmental concentrations showed a slight decrease in microbial counts (5.6×106 to 4.6×106 CFU/mL) after a 24 h incubation for the culturable approach, the predictive elevated concentrations (5 to 100 mg/L) revealed a drastic microbial counts reduction (5.6×106 to 8×102 CFU/mL). The metagenomic data analysis, uncovered that bacterial communities in the control sample were dominated by Proteobacteria, followed by Bacteroidetes and Firmicutes. The taxonomic classification after exposure of microbial communities in various concentrations revealed significant differences in community composition between environmental concentration (Shannon indices between 2.58 to 3.68) and predictive elevated concentrations (Shannon indices between 2.24 to 2.84) (t-test, all P < 0.05). The EE2 enriched seven OTUs were Novosphingobium, Cloacibacterium, Stenotrophomonas, Enterobacteriaceae_unclassified, Stenotrophomonas, Enterobacteriaceae_unclassified and Rhodobacteraceae_unclassified. These results were supported by a dehydrogenase activity (DHA) test, which demonstrated less (about 40%) DHA in predictive elevated concentrations than in environmental concentrations. Notwithstanding, these findings suggest that EE2 may possess potent hormetic effect as evidenced by promotion of microbiome richness and dehydrogenase activity of AS in lower EE2 doses.